Congenital toxoplasmosis as one phenocopy of North Carolina Macular Dystrophy (NCMD/MCDR1) - Small, Kent W. (Am J Ophthalmol Case Rep, 2019)
PURPOSE: To highlight the striking similarities between the lesions of congenital toxoplasmosis (CT) and North Carolina Macular Dystrophy (NCMD) using multimodal imaging including spectral domain optical coherence tomography (SD-OCT). OBSERVATIONS: We are comparing a case report of CT compared to that of NCMD. The case of a 64-year-old man with a lifelong history of decreased vision OD from toxoplasmosis and new onset of central retinal vein occlusion OS. Color fundus photography, spectral domain optical coherence tomography (SD-OCT), and intravenous fluorescein angiography (IVFA) were used as diagnostic imaging tools to demonstrate the similarities and differences between CT and NCMD. In this case, unilateral CT demonstrated a large, excavated, coloboma-like chorioretinal lesion identical to NCMD grade 3. Serology studies were positive for toxoplasmosis. The similarities of CT and NCMD grade 3 using SD-OCT are especially striking. CONCLUSION AND IMPORTANCE: Lesions of CT and NCMD grade 3 can appear identical on clinical exam and are indistinguishable from one another on SD-OCT. Because CT is a phenocopy of NCMD, many cases of the original NCMD family members had been misdiagnosed as CT. North Carolina Macular Dystrophy may be more common than previously realized and bilateral CT cases should be reexamined along with family members and genetic testing performed. Cases of bilateral CT actually may be NCMD cases. Now that the genetic and molecular mechanisms of NCMD are known, these may provide clues into the pathogenesis of CT.